1975
DOI: 10.1088/0031-8949/12/5/007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Interaction, Zeeman and Stark Effects for Excited States in Potassium

Abstract: Using the optical double resonance and level crossing methods, properties of several excited S, P, and D states in 39K were studied. The S and D states were populated using stepwise excitation with the first P state as an intermediate level. An rf lamp and a CW dye laser were used in the first and second excitation steps, respectively. The studied P states were populated in the cascade decay of states, excited with the laser. The following results for the magnetic depole interaction constant a, the Landé gJ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The accuracy of the result thus depends not only on the accuracy of the calculated line strengths, but also on the contribution of the neglected bound states and the continuum. However, calculations made of the polarizabilities of the alkalis, taking into account only the contribution of bound states with principal quantum number n < 20, show fair agreement with experiment [2][3][4]. In the latter calculations the Bates-Darmgaard approximation [1] was applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the result thus depends not only on the accuracy of the calculated line strengths, but also on the contribution of the neglected bound states and the continuum. However, calculations made of the polarizabilities of the alkalis, taking into account only the contribution of bound states with principal quantum number n < 20, show fair agreement with experiment [2][3][4]. In the latter calculations the Bates-Darmgaard approximation [1] was applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, a comparison of experimental polarizabilities with calculated values provides a sensitive test for atomic calculations, especially if the polarizabilities are known in a large number of states. For the alkalis it has been shown that the Coulomb approximation of Bates and Darmgaard [I] leads to fairly good agreement between calculated and experimental values for the tensor polarizabilities [2][3][4]. This is not surprising for these one-electron atoms, considering the predominance of the outer part of the electronic wavefunctions in the dipole matrix elements.…”
Section: Introductionmentioning
confidence: 91%
“…Good HFS measurements exist for all levels of the lines we derive abundances from. The most accurate data come from Bloom & Carr (1960), Dahmen & Penselin (1967), Svanberg (1971), Gupta et al (1973), Belin et al (1975), Sieradzan et al (1997) and Falke et al (2006). We prefer the results of Falke et al (2006) to those of for the 4p 2 P 1/2,3/2 levels, as data from the latter appear not to agree with other measurements (e.g.…”
Section: Potassiummentioning
confidence: 98%
“…This way of inducing level-crossings was preferred, perhaps because magnetic fields were easier to produce and control. Such techniques were used to measure the tensor polarizabilities α 2 of alkali atoms by Svanberg and co-authors (see [4,5,6,7] and references therein). In particular, this method was used in a two-step excitation with a radio-frequency discharge lamp and a narrow-width dye laser [5,6,7].…”
Section: Introductionmentioning
confidence: 99%